A Demographic Analysis of Hearing Impairments among People of Uyghur and Han Ethnicity in Xinjiang, China - Le Wang; Mi Chen; Min Liang; Qin Liu; Hua Yao (Tehran University of Medical Sciences, 2022)
Background: We aimed to investigate the demographic situation relating to people with hearing loss in Xinjiang, the largest province in China. The situation may vary between regions and races. Methods: We conducted a population-based demographic study. We analyzed data obtained from 3931 people with hearing impairments (i.e., from the Han or Uyghur ethnic groups) including children and adults. We accounted for the survey design and sampling size in order to ensure that estimates were regionally representative. Basic characteristics were determined, and an ethnic distribution analysis was conducted based on age group, level of educational, marital status, and level of disability. Results: Of the 3931 participants, 2228 (56.68%) were male and 1703 (43.32%) were female. The mean age of the participants was 46.02 (±19.46) years. Most of the participants (26.20%) were in the 45-59 yr age group. Illiterate people constituted the largest group (34.19%) in the Uyghur population, while a substantial proportion of participants of Han nationality had obtained a junior education (28.98%). The number of unmarried people in both ethnic groups accounted for the highest proportion (more than 70%). Grade 3 was the highest grade observed in the Uyghur population (32.35%), while Grade 1 hearing impairments were the most prevalent in the Han population (28.28%). Conclusion: The difference in basic characteristics between participants of Uyghur and Han ethnicity revealed that different provinces should set different prevention and control targets. Different policy measures should be taken to allocate medical resources and provide rehabilitation services to assist people with hearing impairments in Xinjiang, China. Abbreviations: WHO=World Health Organization, Xinjiang=Xinjiang Uyghur Autonomous Region, YLD=years lived with disability, dB HL=Decibel Hearing Level, SPSS=Statistical Product and Service Solutions, Inc.=Incorporated, IL=Illinois, USA=United States of America; i.e.,=id est (in other words).